2020
DOI: 10.1016/j.ijheatmasstransfer.2020.119306
|View full text |Cite
|
Sign up to set email alerts
|

Role of nanoscale roughness in the heat transfer characteristics of thin film evaporation

Abstract: Thin film evaporation yields high local heat fluxes that contributes significantly to the total heat transfer rate during various two-phase transport processes including pool boiling, flow boiling, and droplet evaporation, among others. Recent studies have shown a strong correlation between the roughness of a surface and its two-phase heat transfer characteristics, but the underlying role of nanoscale surface roughness in thin film evaporation is not fully understood. In the present work, a thin film evaporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This surface roughnessinduced evaporation results in a flatter evaporating meniscus profile. Hu et al [245], in one of their studies, revealed that flow permeability has the most significant impact on thin-film evaporation. Their findings indicate that higher average surface roughness may also restrict evaporation and result in a steeper evaporating meniscus profile.…”
Section: Effect Of Surface Modificationmentioning
confidence: 99%
“…This surface roughnessinduced evaporation results in a flatter evaporating meniscus profile. Hu et al [245], in one of their studies, revealed that flow permeability has the most significant impact on thin-film evaporation. Their findings indicate that higher average surface roughness may also restrict evaporation and result in a steeper evaporating meniscus profile.…”
Section: Effect Of Surface Modificationmentioning
confidence: 99%
“…They also reported an optimum pit-to-pit spacing for maximum boiling enhancement, which was identical to capillary length. Hu et al (2020a) reported that roughness enhances thin-film evaporation when the effect of disjoining pressure is more pronounced and it inhibits thick-film evaporation when the effect of flow permeability is more pronounced.…”
Section: Gouda Et Al (2020) Conducted Experimental Investigation Of P...mentioning
confidence: 99%
“…[24,25] At the same time, wettability engineering (bydesign modulation of the physicochemical surface propertiesboth surface chemistry and physical microstructure) has been known to enhance phase-change heat transfer both in condensation (often by orders of magnitude in the absence of noncondensable gases) and evaporation configurations. [26][27][28][29][30] In view of the above, wettability engineering of AlN surfaces becomes an obvious path for exploiting the favorable properties of these ceramics in developing next-generation thermal management devices that have high CTE compatibility with Silicon. Such properties are apposite for use in hermetically sealed thermal management devices, such as vapor chambers (VCs) and heat pipes, which rely on the phase change of a working fluid.…”
Section: Introductionmentioning
confidence: 99%